Anodal high-definition transcranial direct current stimulation reduces heart rate and modulates heart-rate variability in healthy young people: A randomized cross-controlled trial - Gu, Zhongke; Chen, Wenxiang; Lu, Qian; Dai, Jiansong; Hu, Shugang; Xu, Kai; Geng, Yao; Zhu, Ye; Xu, Boqing; Dai, Wenjun; Shen, Ying (Frontiers in Cardiovascular Medicine, 2022)
Objective: To investigate whether anodal high-definition transcranial current stimulation (HD-tDCS) over the left dorsolateral prefrontal cortex (DLPFC) could modulate the heart rate (HR) and heart-rate variability (HRV) in healthy young people. Methods: Forty healthy young people were enrolled in this randomized crossover trial. The participants were randomized to receive anodal HD-tDCS (n = 20) or sham HD-tDCS (n = 20) over the left DLPFC with a washout period of 1 week. Electrocardiogram (ECG) data were continuously recorded at 20 min before the stimulation, during the session, and 20 min after the session. HR and the time- and frequency-domain indices of the HRV were measured to investigate the activity of the sympathetic and parasympathetic nervous system. Results: Anodal HD-tDCS over the left DLPFC induced a significant decrease in HR and a significant increase in the average of normal-to-normal intervals (AVG NN), low-frequency (LF) power, total power (TP), and LF/high-frequency (HF) ratio in comparison with the sham stimulation and the baseline. However, sham HD-tDCS over the left DLPFC had no significant effect on HR or HRV. Conclusions: Anodal HD-tDCS over the left DLPFC could reduce HR and modulated the HRV in healthy young people. HD-tDCS may show some potential for acutely modulating cardiovascular function.